La colonización rectal por enterobacterales resistentes a carbapenémicos en recién nacidos está relacionada con peores desenlaces clínicos: Un estudio de cohortes (2022)
Background: Carbapenem resistant enterobacteria (CRE) is a global public health problem, especially in vulnerable populations. In newborns, colonization and infection are of particular concern because of the increased morbidity and mortality of these infections. In this study, we searched differences in clinical outcomes between CRE-colonized and CRE-non-colonized newborns. Methods: We performed a retrospective, observational, and longitudinal cohort study for the surveillance of CRE colonization in neonates admitted between 2018 and 2021 in the Neonatal Intensive Care Unit (NICU) of a Children’s hospital in Bogotá, Colombia. The data was analyzed in R 4.0.3. Results: We reviewed 462 clinical records of 4 years-period. We found 21 (4,5%) CRE colonized newborns. Sixty-three CRE-not colonized (CRE-NC) were used as control group. All isolates from rectal culture were Klebsiella pneumoniae. We found that 71,4% of CRE-C and 25% of CRE-NC used antibiotics before admission (p value 0,0005), and 19% and 1,6% in CRE-C and CRE-NC reported previous use of carbapenems (p value 0,01). We found that colonization with CRE increases the risk of sepsis episodes (RR 1,68 CI 1,09 - 2,58), antibiotic requirement (RR 1,45 CI 1,04 – 2,03), carbapenem therapy (RR 6,75 CI 2,32 – 19,66) and, the need for empirical therapy for CRE (RR 4,5 CI 1,4 – 14,4). Conclusions: This study is the first to report worse clinical outcomes among newborns colonized by CRE and, it supports the importance of rectal screening in NICUs, beyond the prevention of outbreaks in this population.